Biochar particle size and Rhizobia strains effect on the uptake and efficiency of nitrogen in lentils. (14th September 2019) - Billah, Muhammad Mutasim; Ahmad, Wiqar; Ali, Murad
Abstract: Biochar has attained significant attention as a beneficial soil amendment amongst growers and researchers. However, the impact of particle size of biochar is yet to be investigated. Here in the present study, we studied three particle sizes (<2 mm, 2–5 mm, and >5 mm) of biochar and two rhizobia strains ( Rhizobium leguminoserum (RL) and Rhizogold (RG)) for their effect on the uptake and efficiency of nitrogen (N) in lentils. The two years experiment followed a randomized complete block design with split plot arrangement replicated three times. The data revealed that grain N, straw N, N uptake, N recovery efficiency (NRE), and N agronomic efficiency (NAE) were maximum with biochar smallest size (<2 mm). However, the N physiological efficiency, number of branches and plant height decreased with reduced particle size. Furthermore, the smallest particle size showed more number of pod plant −1 . Biofertilizer strain (RL and RG) significantly increased the straw N but not the grain N. Both strains showed increased NRE and NAE, however, the RL demonstrated 7% more grain N than the RG. Both strains (RL and RG) demonstrated 16% and 20% increase in number of branches plant −1, 62% and 48% in plant height and 2% and 5% in root length, respectively. The RL strain improved the number of branches plant −1 at the lowest (<2 mm) and medium size (2–5 mm) particles size but both RL and RG strains demonstrated increased plant height under the maximum particle size. These results indicated that a mere increase in surface area with decreasing biochar particle size may not serve for enhancing biofertilizer strains performance since reducing particle size may immobilize the starter N applied. However, reducing particle size effect on N cycling into soil plant system was favorable.